Risks to different populations and age classes of gannets from impacts of offshore wind farms in the southern North Sea. (October 2021) - Pollock, Christopher J.; Lane, Jude V.; Buckingham, Lila; Garthe, Stefan; Jeavons, Ruth; Furness, Robert W.; Hamer, Keith C.
Abstract: The southern North Sea holds the world's highest concentration of offshore wind farms (OWFs). Northern gannets ( Morus bassanus ), a species considered at high risk from OWF impacts, show a strong seasonal peak there in November, but it is unclear which populations and age classes are most at risk of collision with wind turbines. We tagged adult and juvenile gannets at the world's largest colony (Bass Rock) and reviewed two sources of survey data for different age classes to study their movements through southern North Sea waters. Tracked birds showed peak numbers in the southern North Sea in mid-October, with much smaller numbers there during November. Adults were distributed throughout the area, including waters close to OWFs, whereas juveniles were confined to the coast. Survey data indicated high proportions of immature gannets in southern North Sea waters, suggesting higher collision risk than for adults. Gannets present in November may be predominantly from colonies further north than Bass Rock. Highlights: Offshore wind farms in the southern North Sea pose a threat for migrating gannets. Environmental impact assessments need data on ages and populations at risk. We provide insights through combining tracking and survey data. Adults are more at risk than juveniles, whose migration paths are more coastal. Gannets seen later in the year are likely migrating from colonies further north.